Perpustakaan Kejuruteraan: penyusunan semula bilik bacaan di Fakulti Kejuruteraan - Lee, A. (University of Malaya Library, 1986)
The Reading Room at the Faculty of Engineering was absorbed into the University of Malaya Library System in 1985. The Room serves as a library to support the study and research of the undergraduates of the Faculty as well as teaching requirements of the academic staff. The organizational set up of the Library is undergoing overhaul. The Library will focus on collectin materials related to local sudies and also provide basic services such reader services, current awareness and inter-library loans facilities. It also collects the British Standard, Malaysian Standard and related literature.